2009
DOI: 10.1001/jama.301.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Computed Tomography Angiography in Peripheral Arterial Disease

Abstract: age authors to submit papers for consideration as a Clinical Review. Please contact Mary McGrae McDermott, MD, at mdm608@northwestern .edu. Context Computed tomography angiography (CTA) is an increasingly attractive imaging modality for assessing lower extremity peripheral arterial disease (PAD).Objective To determine the accuracy of CTA compared with intra-arterial digital subtraction angiography (DSA) in differentiating extent of disease in patients with PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
1
22

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(224 citation statements)
references
References 39 publications
5
196
1
22
Order By: Relevance
“…While one systemic review and another meta-analysis indicate a lower sensitivity for detecting lower limb arterial thrombosis of [50 % by ultrasound (median sensitivity 90 %, specificity 99 %), duplex sonography was found to have a similarly high specificity as CTA (median sensitivity 97 %, specificity 99.6 %) and MRA (median sensitivity 94 %, specificity 99.2 %) [14,15].…”
Section: Discussionmentioning
confidence: 98%
“…While one systemic review and another meta-analysis indicate a lower sensitivity for detecting lower limb arterial thrombosis of [50 % by ultrasound (median sensitivity 90 %, specificity 99 %), duplex sonography was found to have a similarly high specificity as CTA (median sensitivity 97 %, specificity 99.6 %) and MRA (median sensitivity 94 %, specificity 99.2 %) [14,15].…”
Section: Discussionmentioning
confidence: 98%
“…(32) MSCT is increasingly being used for the more demanding role of screening vascular access routes for TAVI. (33,34) The advantage is that an overview of all potential vascular access routes, including transfemoral, -subclavian or -apical may be obtained, (35) (Figure 4).…”
Section: Vascular Accessmentioning
confidence: 99%
“…Recent studies using direct perforator injection combined with static and dynamic computed tomographic angiography have shown that each perforator holds a unique vascular territory that was, consequently, termed the perforasome. 46 This perforasome has a highly complex and variable vascular territory and, like the angiosomes, perforasomes are linked by direct and indirect vessels. Direct linking vessels are defined as large vessels communicating directly from one perforator to the next that are able to take over adjacent perforasomes through an interperforator flow mechanism.…”
Section: Evolution Of the Perforator Flapmentioning
confidence: 99%
“…30,31,[44][45][46] It does not necessitate arterial puncture or day-care admittance and, as a result of increased scan speed and improved spatial resolution, the recently introduced multislice technology may even offer improved quality for angiographic imaging. 30,31,[44][45][46][47] Three-dimensional reconstruction protocols of CT-scans permit the arteries and veins to be viewed from any perspective and allow vascular diameters to be accurately measured. These advantages can be contrasted with limited disadvantages such as the need for larger amounts of contrast medium, the need to optimize the timing of the contrast bolus and the scan, and a fair amount of radiation for the scanning protocol.…”
Section: Pre-operative Assessment Of the Internal Mammary Vascular Symentioning
confidence: 99%